1998
DOI: 10.1590/s1516-31801998000200005
|View full text |Cite
|
Sign up to set email alerts
|

How should PCNA be assessed? Total of stained cells or only the most intensely stained ones?

Abstract: Higher nuclear (NG3) and histological (HGIII) grading, associated with a high PCNA index (> 50), distinguish high-risk patients, and it is more appropriate considering all the stained cells as representative of PCNA indices, thus reflecting tumor aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(73 reference statements)
0
5
0
3
Order By: Relevance
“…In this report, we considered the total PCNA positive cells regardless of the staining intensity. Kemp et al (1998) demonstrated that the total of stained cells was more representative of tumor aggressiveness and were better correlated with the anatomopathological parameters in breast cancer than the intensity of staining.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we considered the total PCNA positive cells regardless of the staining intensity. Kemp et al (1998) demonstrated that the total of stained cells was more representative of tumor aggressiveness and were better correlated with the anatomopathological parameters in breast cancer than the intensity of staining.…”
Section: Discussionmentioning
confidence: 99%
“…No epitélio mamário de tecido adjacente ao fibroadenoma de mulheres no menacme, o tamoxifeno reduziu a proliferação do lóbulo medido pelo índice mitótico, volume nuclear, número de lisossomos, PCNA e MIB-1 14,17,22 . Estes trabalhos demonstraram também que o tamoxifeno atua, de forma antagônica ao estrogênio, no epitélio da mama normal de mulheres no menacme.…”
Section: Discussionunclassified
“…A contagem de células foi feita por meio de objetiva de 40 vezes, com aumento final de 400 vezes, contando-se, no mínimo, 500 células a partir da área com maior reação do Ki-67, com aleatorização dos campos posteriores. Considerou-se positiva a célula cujo núcleo exibisse a coloração castanha, independentemente da disposição e intensidade 22 .…”
Section: Pacientes E Métodosunclassified
“…PCNA (proliferating cell nuclear antigen) is a subunit of DNA polymerase and cell cycle-dependent protein whose maximum appearance in the S phase. Some research shows that the expression of PCNA is connection with the low grade tissues[ 35 , 36 ]. Wang JJ found that the gene expression of nuclear PCNA increased obviously, and the labeling index of PCNA was 15.…”
Section: Reviewmentioning
confidence: 99%